2022
DOI: 10.4274/tjo.galenos.2021.24376
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approach in Intraocular Tumors

Abstract: Surgery in intraocular tumors is done for excision/biopsy and the management of complications secondary to the treatment of these tumors. Excision/biopsy of intraocular tumors can be done via fine-needle aspiration biopsy (FNAB), transretinal biopsy (TRB), partial lamellar sclerouvectomy (PLSU), and endoresection. FNAB, TRB, and PLSU can be used in tumors that cannot be diagnosed by clinical examination and other ancillary testing methods. PLSU is employed in tumors involving the iridociliary region and choroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 93 publications
(146 reference statements)
0
4
1
Order By: Relevance
“…These findings were not much different from previous studies which reported that the incidence of these clinical features varied with range between 17.92% -63.25% (Ackuaku-Dogbe, Akpalu and Abaidoo, 2017;Muralidhar, Das and Tiple, 2020). These two clinical features are nonspecific features of TED and are manifestations of a soft tissue inflammatory process which is often an early sign of TED (Şahlı and Gündüz, 2017).…”
Section: Discussioncontrasting
confidence: 62%
“…These findings were not much different from previous studies which reported that the incidence of these clinical features varied with range between 17.92% -63.25% (Ackuaku-Dogbe, Akpalu and Abaidoo, 2017;Muralidhar, Das and Tiple, 2020). These two clinical features are nonspecific features of TED and are manifestations of a soft tissue inflammatory process which is often an early sign of TED (Şahlı and Gündüz, 2017).…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, we provided a new option for locating intraocular masses without vitrectomy. This endoilluminationassisted localization technique without vitrectomy has been applied in endolaser photocoagulation via a two-port pars plana nonvitrectomy approach [ [3] ]and endoilluminator-assisted scleral buckling [ [1] ]for the treatment of stage 3 Coats' disease and has achieved good results. The technology has many advantages, rst of all, it solves the problem of inaccurate positioning in traditional positioning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Endoresection surgery [ [3] ]refers to intraocular tumor excision using vitreoretinal surgery methods. This surgical method can disrupt the normal tissue structure of the eye, resulting in a variety of complications[ [4] ], such as silicone oil dependence, retinal detachment, ocular hypertension or hypotension, vitreous hemorrhage, epiretinal membrane, eyeball atrophy, macular hole, choroidal neovascularization, proliferative vitreoretinopathy, and endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Surgical removal via exoresection is performed in iridociliary, ciliary body, and anterior choroidal tumors. [9][10][11] Endoresection is usually performed in irradiated postequatorial choroidal melanomas to prevent complications related to toxic tumor syndrome and recurrences. [11][12][13] Radiotherapy (RT), applied either as brachytherapy (plaque RT) or teletherapy [proton beam therapy, stereotactic radiosurgery (SRS)] is the most common treatment option for medium sized PUM.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Endoresection is usually performed in irradiated postequatorial choroidal melanomas to prevent complications related to toxic tumor syndrome and recurrences. [11][12][13] Radiotherapy (RT), applied either as brachytherapy (plaque RT) or teletherapy [proton beam therapy, stereotactic radiosurgery (SRS)] is the most common treatment option for medium sized PUM. [14][15][16][17][18][19][20][21][22] Plaque RT approaches with Ruthenium-106 (Ru-106), Iodine-125 (I-125), and less commonly Palladium-103 radioisotopes are widely used worldwide with proven efficacy in local tumor control.…”
Section: Introductionmentioning
confidence: 99%